Biogeografía histórica y diversificación del género allobates (anura : aromobatidae) - Martínez, Andrés Felipe Jaramillo (2021)
The nurse-frogs, Allobates, include 57 species distributed in the Neotropics, from Nicaragua to the south of Atlantic forest in Brazil inhabiting different ecosystems. Through their taxonomic history, some species were transferred to another generas of Dendrobatoidea by the few diagnosable characters due to the conservation of the external morphology. Also, this was the reason which some species were redescribed to understand their intraspecific variation. For other hand, the phylogenetical hypotheses in previously studies are incongruent because each one use different optimization methods and character and taxon sampling. Moreover, is unknown which historical mechanism originate the current diversity in the genera. In this study was evaluated the taxonomy, systematics, biogeography and diversification at different hierarchical levels integrating morphology, osteology, behavior and molecules. For this reason, Allobates trilineatus was described based on new especimens collected from the type locality, for the first time we provide acoustics and mitochondrial sequences data, also, we comment about the possible cryptic diversity under this binomial name. Furthermore, we describe a new species of Allobates closely related to A. trilineatus, based in morphological, acoustics, and molecular evidence. For other hand, it reveals for the first time the mitonuclear discordance in a clade conformed by A. juami/insperatus probably caused by introgression or incomplete lineage sorting, and was discussed the possible biogeographical scenario that might give the origin of this complex evolutionary history, also, was described a remarkable new species from this complex. Similarly, we demonstrated that the current Allobates diversity are subestimated where there are more 21 % more species that are missing, moreover, the mega wetland of Pebas have a big impact in the diversification where the most the species XVI accumulation occurred between 14 and 10 Mya providing new habitas which the species can colonized and speciate. Finally, we demonstrate instable zones in the phylogenetic hypothesis caused by the molecular character optimization, possible generated by missing data and complex evolutionary histories. Moreover, we reveal that each Amazonian area historically has unique diversification mode seen through dispersal, vicariance and extirpation events, also, the current specie richness distribution pattern in Amazonia is explained by the time of the first colonization and the speciation rate. We highlighted the importance the made studies at different hierarchical level integrating morphology, behavior and molecules to resolve complex taxonomy or evolutionary histories.